La proposta gramatical del P. Lluís Fullana i Mira - Simbor Roig, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
By studying step by step, from beginnig to end, Father Fullana's grammatical studies, Prof. Simbor offers the reader the possibility of following the ideological evolution of this outstanding Valencian grammarian during three main periods: A unitarian one (1902-1915), a secessionist one (1915-1932), and a final one (1932-1948), when, after being the first to accept and to sign the unitarian ortography of Castelló de la Plana, he seems to have closed the process by accepting P. Fabra's proposals.